Concord Credit Union : evolving employees roles in the post-crisis, digitally-driven banking industry - Kleinsmith, Niela; Koene, Bas, 1966-; Perez, Coralie (London : Rotterdam School of Management, Erasmus University, 2018)
In May 2017, Paul Beaumont, CEO of Concord Credit Union, one of the largest European credit unions, or mutualist banks, reflected on how the current evolution of the banking industry would affect his institution. Faced with increased regulation, the need for cost-cutting, industry overcapacity, rapid growth among non-traditional competitors, and increasing customer demands for flexible and digital options, retail banks were navigating uncertain industrial terrain, and needed to decide which would be the surest path for their long-term future. Few banks, if any, had a clear strategic vision. After years of developing increasingly complex products and services, with the resulting financial crisis and subsequent tightening of regulations, banks were now once again focusing their growth efforts on the customer. Restructuring was a given, but how? As a credit union, Concord Credit Union (CCU) was owned and operated by its customers; its mandate was one of solvency and high customer service levels, rather than high profitability, as with most other banks. CCU customers belonged to the traditional side of the banking spectrum, demanding digital options while retaining the need for physical contact with representatives from the bank. But what about the next generation of customers? Growth was now intrinsically linked to a digital offering, much more than to a physical footprint of offices, as had been the case only a few decades ago. How should Beaumont approach the wave-pool of technology before him? The choices he made for the bank's long-term growth would have an immediate impact on his employees, who were also customers and owners of the bank. Which path would he choose, and what would this mean for his company and his employees? Any choice would be a bet on the future.
Originally Published InKleinsmith, N., Koene, B., & Perez, C. (2018). Concord Credit Union: Evolving Employees Roles in the Post-Crisis, Digitally-Driven Banking Industry. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Relationship banking -- Case studies